Molecular relationships of Campomanesia xanthocarpa within Myrtaceae based on the complete plastome sequence and on the plastid ycf2 gene - Machado, Lilian de Oliveira (Genet Mol Biol, 2020)
Plastomes are very informative structures for comparative phylogenetic and evolutionary analyses. We sequenced and analyzed the complete plastome of Campomanesia xanthocarpa and compared its gene order, structure, and evolutionary characteristics within Myrtaceae. Analyzing 48 species of Myrtaceae, we identified six genes representing ‘hotspots’ of variability within the plastomes (ycf2, atpA, rpoC2, pcbE, ndhH and rps16), and performed phylogenetic analyses based on: (i) the ycf2 gene, (ii) all the six genes identified as ‘hotspots’ of variability, and (iii) the genes identified as ‘hotspots’ of variability, except the ycf2 gene. The structure, gene order, and gene content of the C. xanthocarpa plastome are similar to other Myrtaceae species. Phylogenetic analyses revealed the ycf2 gene as a promissing region for barcoding within this family, having also a robust phylogenetic signal. The synonymous and nonsynonymous substitution rates and the Ka/Ks ratio revealed low values for the ycf2 gene among C. xanthocarpa and the other 47 analyzed species of Myrtaceae, with moderate purifying selection acting on this gene. The average nucleotide identity (ANI) analysis of the whole plastomes produced phylogenetic trees supporting the monophyly of three Myrtaceae tribes. The findings of this study provide support for planning conservation, breeding, and biotechnological programs for this species.